Achieving over 15% Efficiency in Solution-Processed Cu(In,Ga)(S,Se)(2) Thin-Film Solar Cells via a Heterogeneous-Formation-Induced Benign p-n Junction Interface - Kim, Da-Seul; Park, Gi Soon; Kim, Byungwoo; Bae, Soohyun; Park, Sang Yeun; Oh, Hyung-Suk; Lee, Ung; Ko, Doo-Hyun; Kim, Jihyun; Min, Byoung Koun (American Chemical Society, 2021)
Cu(In,Ga)(S,Se)(2) (CIGS) thin-film solar cells have attracted considerable interest in the field of photovoltaic devices due to their high efficiency and great potential for diverse applications. While CdS has been the most favorable n-type semiconductor because of its excellent lattice-match and electronic band alignment with p-type CIGS, its narrow optical band gap (similar to 2.4 eV) has limited light absorption in underlying CIGS absorber films. Reducing the thickness of CdS films to increase the short-circuit current-density has been less effective due to the following decrease in the open-circuit voltage. To overcome this trade- off between the main parameters, we controlled the formation mechanism of CdS films in chemical bath deposition and established its direct correlation with the properties of p-n junctions. Interestingly, a heterogeneous CdS film formation was found to have a synergetic effect with its ammonia bath solution, effectively reducing charge carrier loss from the shunt paths and interface recombination of CIGS/CdS junctions. With these electrical benefits, the trade-off was successfully alleviated and our best device achieved a power conversion efficiency of 15.6%, which is one of the state-of-the-art CIGS thin-film solar cells prepared using solution-processing techniques.